Infectious complications caused by carbapenemase-producing Enterobacterales in patients with hematological disorders - K. S. Tandilova; G. A. Klyasova (Онкогематология, 2019)
Mortality rates approaching 60 % have been reported in hematological patients with infections caused by carbapenemase-producing Enterobacterales. The incidence of these infections is rapidly increasing, whereas the therapeutic options are limited. This review represents characteristics of infections caused by carbapenemase-producing Enterobacterales in patients with hematological disorders, highlights risk factors and management options of these infections.